Innovation in Public Service Through the Electronic Self-Registration System (E-Pentole) at Bhayangkara Hospital Surabaya - Mochamad Farros Pambudi Luhur; Trenda Aktiva Oktariyanda; Eva Hany Fanida; Meirinawati M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Public services in the health sector are required to be more effective, efficient, and responsive to community needs. One effort to improve service quality is through information technology-based innovation. This study aims to analyze public service innovation through the Electronic Total Dewe Registration (E-Pentole) system at Bhayangkara Hospital Surabaya. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through interviews, observation, and documentation. The research analysis uses Everett M. Rogers' Diffusion of Innovation theory, which includes five indicators: relative advantage, suitability, complexity, trialability, and visibility of results. The results show that the implementation of E-Pentole can improve the efficiency of the patient registration process, reduce service queues, and simplify the management of hospital administrative data. This system is considered to have advantages over manual systems because it is faster, more practical, and integrated with patient medical records. However, challenges remain, such as varying levels of patient technology literacy and the need for increased public outreach. Therefore, continuous system development is needed through increased staff training, system maintenance, and the development of digital service features to support more optimal health services.